2006
DOI: 10.1007/s00467-006-0066-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and superoxide in rat mesangial cells: modulation by C-reactive protein

Abstract: CRP enhances superoxide release in RMC, which in turn inactivates NO and reduces net production. The functional relevance of these CRP-induced changes is supported by increased expression of HSP90 in RMC exposed to the mediator. These findings suggest that systemic inflammation, which contributes to the pathogenesis of atherosclerosis, may play a role in the progression of kidney disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 44 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…Prasad [32] have shown that in neutrophils, CRP significantly and dose-dependently induces superoxide anion release in vitro, however, no mechanistic studies were undertaken. Exposure of rat mesangial cells to CRP for 60 min led to a dose-dependent increase in superoxide anion release that was nearly threefold greater than that in the control conditions (p < 0.0001) [33]. They also showed that co-incubation with DPI (10 μM) prevented the increase in superoxide production by rat mesangial cells induced by CRP (100 μg/mL).…”
Section: Discussionmentioning
confidence: 90%
“…Prasad [32] have shown that in neutrophils, CRP significantly and dose-dependently induces superoxide anion release in vitro, however, no mechanistic studies were undertaken. Exposure of rat mesangial cells to CRP for 60 min led to a dose-dependent increase in superoxide anion release that was nearly threefold greater than that in the control conditions (p < 0.0001) [33]. They also showed that co-incubation with DPI (10 μM) prevented the increase in superoxide production by rat mesangial cells induced by CRP (100 μg/mL).…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested that a glucose-induced impairment of dimethylarginine dimethylaminohydrolase causes ADMA accumulation and may contribute to endothelial vasodilator dysfunction in diabetes mellitus [22]. C-reactive protein is a well-studied inflammatory marker in the setting of cardiovascular disease; and lastly, it has been suggested that increased CRP has also been associated with endothelial dysfunction and the progression of atherosclerosis [23]. In our study, plasma baseline CRP concentrations were increased at the prediabetic state, glucose loading caused an elevation in plasma CRP concentrations, and plasma CRP levels were found to be correlated with plasma ADMA levels at the prediabetic state.…”
Section: Discussionmentioning
confidence: 99%
“…One theory is that renal dysfunction is related to inflammation through the reduction in the nitric oxide synthase activity [26]. Nitric oxide synthase is linked to inflammation through its role in the formation of peroxynitrate, an important mediator of the immune response.…”
Section: Discussionmentioning
confidence: 99%